2016
DOI: 10.1111/fima.12123
|View full text |Cite
|
Sign up to set email alerts
|

Informed Trading in Corporate Bonds Prior to Earnings Announcements

Abstract: This paper examines the information content of corporate bond trading prior to earnings announcements using data from both NAIC and TRACE. We find that the direction of preannouncement bond trading is closely related to earnings surprises. This link is most evident prior to negative news and in high-yield bonds. Further, abnormal bond trading during the preannouncement period can help predict both earnings surprises and post-announcement bond returns. Such predictive ability of bond trading largely originates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(11 citation statements)
references
References 70 publications
(88 reference statements)
0
11
0
Order By: Relevance
“…Studies have highlighted a decrease in equity market liquidity around earnings announcements due to increased information asymmetry (e.g., Lee, Mucklow, and Ready [1993], Krinsky and Lee [1996]). Given the significant amount of informed trading found around earnings announcements in corporate bond markets (e.g., Wei and Zhou [2016], Even‐Tov [2017]), we expect similar increases in information asymmetry in corporate bond markets. Such an increase is another important determinant of bond market liquidity around earnings announcements, so we explore its interactions with the decrease in search and bargaining frictions around earnings announcements.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…Studies have highlighted a decrease in equity market liquidity around earnings announcements due to increased information asymmetry (e.g., Lee, Mucklow, and Ready [1993], Krinsky and Lee [1996]). Given the significant amount of informed trading found around earnings announcements in corporate bond markets (e.g., Wei and Zhou [2016], Even‐Tov [2017]), we expect similar increases in information asymmetry in corporate bond markets. Such an increase is another important determinant of bond market liquidity around earnings announcements, so we explore its interactions with the decrease in search and bargaining frictions around earnings announcements.…”
Section: Resultsmentioning
confidence: 86%
“…Unsurprisingly, given the resources available to these investors, informed traders are active in corporate bond markets. 13 For instance, studies find a significant amount of informed trading around earnings announcements (e.g., Wei and Zhou [2016], Even-Tov [2017]). However, despite the fact that institutional investors are more likely to be informed, they will typically face lower transaction costs in OTC markets, due to their superior search and bargaining capabilities (e.g., Harris and Piwowar [2006], Green, Hollifield, and Schürhoff [2007b], Cuny, Even-Tov, and Watts [2021]).…”
Section: Institutional Background and Theoretical Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…Signaling theory is also widely used in explaining investment decisions (Alsos & Ljunggren, 2017). In their research, Wei & Zhou (2016) found that before the publication of an income statement, bond trading activities tended to increase due to asymmetrical information from new signals.…”
Section: Signaling Theorymentioning
confidence: 99%
“…1 1 Bessembinder et al (2009) discuss major bond event studies to that date. More recent bond event studies, with databases in parentheses, include Chava, Ganduri, and Ornthanalai (2012) (TRACE and credit default swaps (CDS)), Clayton (2011) (TRACE, Lehman Brothers, and NAIC), Gao et al (2011) (TRACE), Klein and Zur (2011) (FISD and TRACE), Wei and Zhou (2012) In the seminal paper on bond event study methods, Bessembinder, Kahle, Maxwell, and Xu (2009) (hereafter BKMX) show that: (1) among the bond databases they examine, the TRACE data yield the most powerful event test statistics, (2) t-test statistics are mis-specified for monthly data, and (3) non-parametric tests are better specified and more powerful than the t-test -though likely to be less powerful when bond returns are skewed. For TRACE based event studies, they recommend:…”
Section: Introductionmentioning
confidence: 99%